Do Board of Directors Ensure Quality of Disclosures in Annual Reports? - Jarwal, Devendra (Shanlax International Journal of Management, 2022)
A company’s published annual report is the primary channel of communication with shareholders and shareholders use these reports as a tool to monitor the activities of the Companies. The present study is an attempt to assess the effectiveness of annual reports in communication and its utility in monitoring affairs of the companies. The prime focus of this study is to rate management discussion and analysis on perceived risk factors of the company and the disclosure quality of risk perceptions of the management. The purpose of the study is to explore the quality of disclosures in the annual reports hence exploratory-qualitative analysis technique has been applied. Reports of selected companies were analysed and results were discussed with selected stakeholders to corroborate findings with the existing patters in disclosures. The study concludes that the level of reporting is associated with stages of maturity of a company and during a larger phase of a company quality of disclosure remains irrelevant to management as well as to shareholders. Existing researches on the subject have identified various factors influencing comprehensiveness of disclosures in the annual reports while this research has explored a new theory of irrelevance in disclosing crucial risk-related perceptions.